A review of congenital diaphragmatic hernia. Issue 1 (February 2013) - Marlow, Jay; Thomas, Joseph
Abstract: Background : Congenital diaphragmatic hernia (CDH) is a simple diaphragmatic defect that is seen frequently in antenatal scans. Though the surgical repair is relatively easy in the neonate, the mortality is high due to pulmonary hypoplasia and pulmonary vascular changes. Materials and Methods : The goals of prenatal imaging are to establish the diagnosis. Assessment in a tertiary scanning center would identify prognostic factors which assist in counselling and planning antenatal management. However, the pulmonary hypoplasia associated with the CDH in moderate and severe cases makes the prognosis poor. Conclusions : Fetal intervention such as, fetal tracheal occlusion, is being trialled and may change the outcomes in the future.